(3GdChGFds - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY QJHg GdCOH hOaYjI hCYdi efRdg Cgd GdYde hMGedjg hbO QCjJ GcKQ GdNGUg hLd GdYGeg s
(3BNQgG (B:s
(3gfG BNQ hGNQL GdjfG ef GdChGFd , Ef NQL TJi BNQ GdMbfGg Hg hbO aQZfG ef EedGFg jhe GdCQHYGA dCQHY YTQg NdJ ef TYHGf Sfg (B395 (3hMSHfG Gddg hMOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B560s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B914 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B40 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B((3JGQjN (B48) s
Keywords: (3GdJGQjNs